Insurance that Works : What Drives Insurance Sector Development in the Republic of Rwanda, and What are the Opportunities Ahead? - World Bank Group (World Bank, Washington, DC, 2020)
The study examines a range of data sets to develop the analytical basis for the review, conclusions and recommendations. Insurance development is driven by a large range of factors, some of which can be better observed than others. Data is important but understanding what it means is also important. Benchmarking results, including cross country analysis and other research to understand the meaning of calculated values, is one element that is under‐represented in industry analysis. Demand and potential demand for insurance are also considered considering the nature and level of risk being faced as the basis for the examination of insurance markets effectively assuming individuals and entities should and would take out insurance if they were offered it against these risks. Other dimensions examine perceptions of risk, insurance as a solution, and then other barriers to access that may limit the extent that a risk that can be insured coverts into a risk that is insured. In this section, we approach both a range of potential risks and their trends along with data about clients. Through the report, elements of the regulatory and supervisory arrangements are addressed as they are relevant. For those that are not specifically raised in these sections, a further section covers the remaining review of regulatory arrangements as needed. The diagnostic review has also been conducted through an extensive set of fact‐finding stakeholder meetings to gather input, validate and supplement the data‐based analysis.